2008
DOI: 10.1007/s11064-008-9748-z
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of Oligodendrocyte Progenitor Cell Migration by a PDGF-A Activated Extracellular Regulated Kinase (ERK) Signaling Pathway

Abstract: During CNS development, oligodendrocyte progenitor (OP) cells migrate from germinal zones to presumptive white matter tracts to generate myelinating oligodendrocytes. In vitro and in vivo studies indicate that platelet-derived growth factor-A (PDGF-A) is a potent chemoattractant for OP cells and important for normal distribution throughout the developing CNS. However, PDGF-A does not localize in concentration gradients corresponding to OP migratory pathways, as would be expected for a chemoattractant to direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
69
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 50 publications
(76 reference statements)
9
69
0
Order By: Relevance
“…Initially, cells were plated at a density of 4 x 10 5 /cm 2 in standard hMSC medium [DMEM supplemented with 10% foetal bovine These experiments are the first to explore the migration of hMSCs using the agarose drop assay which allows for quantitative analysis of migration and assessment of cell morphology in response to changes in culture medium over 72 h, although direction and velocity of migration are not assessed. 21 The results broadly concur with the findings of other investigators who have studied chemokine-induced migration of hMSCs ( Table 1). [22][23][24][25][26][27][28][29][30][31] A notable exception was the failure to demonstrate migration of hMSCs in response to MCP-1 by Ringe et al 26 and CroitoruLamoury et al 22 although the latter did demonstrate chemotaxis following pre-treatment with interferon-β.…”
Section: Methodssupporting
confidence: 91%
“…Initially, cells were plated at a density of 4 x 10 5 /cm 2 in standard hMSC medium [DMEM supplemented with 10% foetal bovine These experiments are the first to explore the migration of hMSCs using the agarose drop assay which allows for quantitative analysis of migration and assessment of cell morphology in response to changes in culture medium over 72 h, although direction and velocity of migration are not assessed. 21 The results broadly concur with the findings of other investigators who have studied chemokine-induced migration of hMSCs ( Table 1). [22][23][24][25][26][27][28][29][30][31] A notable exception was the failure to demonstrate migration of hMSCs in response to MCP-1 by Ringe et al 26 and CroitoruLamoury et al 22 although the latter did demonstrate chemotaxis following pre-treatment with interferon-β.…”
Section: Methodssupporting
confidence: 91%
“…First, we demonstrated that HI caused an increase in cells capable of migration both at the presumptive source and at the destination. Following HI injury, we found increased numbers of cells in the SVZ that expressed PDGFR ␣ which is found predominantly in migratory and mitotic OPCs [Rivers et al, 2008;Frost et al, 2009]. We also found increased PDGFR ␣ + cells in the adjacent striatum.…”
Section: Discussionmentioning
confidence: 64%
“…We used immunofluorescence to probe for PDGFR ␣ in order to characterize changes in OPCs [Rivers et al, 2008;Frost et al, 2009] …”
Section: Postnatal Hi Causes Regional Increases In Pdgfr ␣ + Cellsmentioning
confidence: 99%
“…Several studies have implicated the PI3K/Akt pathway in the proliferation, migration, or survival of OPCs [16][17][18][19][20][21][22] , so we examined the effects of TAPP1 inhibition on the expression of Akt during OPC differentiation. Surprisingly, TAPP1…”
Section: Tapp1 Inhibition Alters Erk1/2 Expressionmentioning
confidence: 99%